2016
DOI: 10.1016/j.powtec.2015.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Determining the significance of flotation variables on froth rheology using a central composite rotatable design

Abstract: Determining the significance of flotation variables on froth rheology using a central composite rotatable design, Powder Technology (2015Technology ( ), doi: 10.1016Technology ( /j.powtec.2015 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…froth height, gas rate, impeller speed, feed particle size and feed grade) on froth rheology. A Central Composite Rotatable Design (CCRD) study was carried out, in which 33 flotation tests were performed in a 20 L continuously-operated flotation cell [20]. The froth rheology was measured using a method developed recently by the authors [21].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…froth height, gas rate, impeller speed, feed particle size and feed grade) on froth rheology. A Central Composite Rotatable Design (CCRD) study was carried out, in which 33 flotation tests were performed in a 20 L continuously-operated flotation cell [20]. The froth rheology was measured using a method developed recently by the authors [21].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Froth flow is also an irreversible process, which involves the rearrangement of bubbles and changes in bubble surface area [13]. In a series of flotation tests, in both pilot and industrial scale, conducted by [87][88][89][90]; the measured froths showed pseudoplastic behaviour. In their flotation tests, flotation variables including frother dosage, feed grade, air rate, froth depth, impeller speed, and valuable mineral particle size were investigated with respect to froth rheology [88,89].…”
Section: Variables Affecting Froth Rheologymentioning
confidence: 99%
“…In their flotation tests, flotation variables including frother dosage, feed grade, air rate, froth depth, impeller speed, and valuable mineral particle size were investigated with respect to froth rheology [88,89]. Table 2 shows the variables that significantly affected froth rheology [89]. Feed grade and froth height were positively correlated with froth apparent viscosity, whereas particle size and impeller speed were negatively correlated with froth apparent viscosity.…”
Section: Variables Affecting Froth Rheologymentioning
confidence: 99%
See 1 more Smart Citation
“…The central composite rotatable design model (CCRD) was used as experimental design at different fields [15][16][17]. In the present study, the weight of the Albizia plant, concentration of dye, and time of adsorption were identified as main parameters, while the efficiency of adsorption was taken as an objective variable in the central composite rotatable design model (CCRD).…”
Section: Central Composite Rotatable Design Modelmentioning
confidence: 99%